Kebutuhan Pelayanan Sosial bagi Lanjut Usia Terlantar - Rusmiyati, Chatarina (Babes Litbang Yankessos, 2020)
This study aimed to determine the implementation of social assistance through home care services and its benefits for neglected elderly people. The research location was in Jeneponto Regency, South Sulawesi, Republic of Indonesia with consideration that there were quite a lot of neglected elderly people in the region and social assistance through home care had been carried out by the Elderly Social Welfare Institution (LKS LU). The study used a qualitative descriptive approach. Data collection was carried out by interview using interview guides and observations. The data collected was analyzed descriptively to illustrate the implementation of social assistance through home care and its benefits for the elderly. The results showed that social assistance through home care in Jeneponto District carried out by the Bakti Jaya Elderly Social Welfare Institution and Ummi Naharia Elderly Social Welfare Institute had been going well. Home care services took the form of social care, social assistance and meeting the basic needs of the elderly. Elderly recipients of home care social assistance were happy with the attention given by the mentors. They were happy and satisfied with the assistance received, such as milk, biscuits, cereal drinks, tea, coffee and other needs as requested. The existence of a social security program for the elderly so far is expected to continue to exist as a form of government attention to all members of the community, especially for neglected elderly.Â Keywords: needs; social services; neglected elderly; Social Welfare Institution for Elderly (LKS LU).